2007
DOI: 10.1002/ajmg.b.30544
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in dopamine receptor DRD1 and DRD2 genes and psychopathological and extrapyramidal symptoms in patients on long‐term antipsychotic treatment

Abstract: DRD(1) and DRD(2) receptor gene variants have been associated with clinical aspects of schizophrenia; however only specific features were analyzed in different samples. To assess the complex interaction between genetic and clinical factors, we studied the possible cross-interactions between DRD1 and DRD2 dopamine receptor gene polymorphisms, symptomatology of schizophrenia and schizoaffective disorders, and the occurrence of treatment induced side effects taking into consideration possible clinical confounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 62 publications
0
22
1
2
Order By: Relevance
“…Nevertheless, case-control genetic association studies analyzing the role of DRD1 in schizophrenia have revealed negative results [Campion et al, 1994;Cichon et al, 1996;Kojima et al, 1999;Iwata et al, 2003;Hoogendoorn et al, 2005;Dmitrzak-Weglarz et al, 2006;Dolzan et al, 2007;Talkowski et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, case-control genetic association studies analyzing the role of DRD1 in schizophrenia have revealed negative results [Campion et al, 1994;Cichon et al, 1996;Kojima et al, 1999;Iwata et al, 2003;Hoogendoorn et al, 2005;Dmitrzak-Weglarz et al, 2006;Dolzan et al, 2007;Talkowski et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Using the candidate gene approach, several polymorphisms within genes encoding receptors for dopamine and serotonin have been studied for association with AIP, but findings are not conclusive (Gunes et al 2008;Kaiser et al 2002;Nakazono et al 2005;Güzey et al 2007;Dolzan et al 2007;Al Hadithy et al 2008). Associations have been reported for the VNTR polymorphism in DAT1 (Güzey et al 2007), Taq1, and141CIns/Del variants in DRD2 (Guzey et al 2007;Al Hadithy et al 2008), and the HTR2C polymorphism Cys23Ser (Gunes et al 2008;Al Hadithy et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For both polymorphisms, the search yielded nine studies. Five studies could not be included either because categorical data were not used 61,69 or data were not reported. 56,59,60 No large or significant pooled OR was found for the alleles or genotypes for Ser311Cys 58,[66][67][68] or for À141C Ins/Del 27,66-68 (results available upon request).…”
mentioning
confidence: 99%